Potentials for energy savings and carbon dioxide emissions reduction in cement industry - Sarfraz, Shoaib; Sherif, Ziyad; Drewniok, Michal; Bolson, Natanael; Cullen, Jonathan; Purnell, Phil; Jolly, Mark R.; Salonitis, Konstantinos (Springer, 2025)
Cement production accounts for 7% of global carbon dioxide emissions, 3 to 4% of greenhouse gas emissions, and 7% of global industrial energy use. Cement demand is continuously increasing due to the rising worldwide population and urbanisation trends, as well as infrastructure development needs. By 2050, global cement production is expected to increase by 12 to 23% from its current level. Following the net-zero carbon 2050 agenda, both energy and emissions must be significantly reduced. Different production routes exist to produce cement that differs in energy intensity as well as carbon intensity. Similarly, a range of values exists related to energy and emissions for the major cement production stages i.e., raw meal preparation, clinkerisation and cement grinding. The same is the case with cement types produced. This study presents a literature review-based investigation and comparison of cement production practices in terms of energy consumption and CO2 emissions. This will provide perspectives to the cement industry by identifying approaches that are the least energy and emissions intensive.
Keywords: 4005 Civil Engineering; 40 Engineering; 33 Built Environment and Design; 3302 Building; 13 Climate Action; 7 Affordable and Clean Energy